2012
DOI: 10.5935/1678-9741.20120004
|View full text |Cite
|
Sign up to set email alerts
|

Resultados clínicos e metabólicos da abreviação do jejum com carboidratos na revascularização cirúrgica do miocárdio

Abstract: Resultados clínicos e metabólicos da abreviação do jejum com carboidratos na revascularização cirúrgica do miocárdioClinical and metabolic results of fasting abbreviation with carbohydrates in coronary artery bypass graft surgery Rev Bras Cir Cardiovasc 2012;27(1):7-17

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
2
25
0
5
Order By: Relevance
“…These results are in agreement with two previous studies that document speedy recovery and less need of vasoactive drugs, if oral CHO loading is done prior to cardiac surgery [7, 8]. Curtailing of preoperative fasting, with CHO loading, is no longer a novelty approach [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with two previous studies that document speedy recovery and less need of vasoactive drugs, if oral CHO loading is done prior to cardiac surgery [7, 8]. Curtailing of preoperative fasting, with CHO loading, is no longer a novelty approach [9].…”
Section: Discussionsupporting
confidence: 91%
“…In cardiac surgery specifically, some randomized trials have shown that CHO loading 2 h before inducing anesthesia will reduce ICU and hospital stays while reducing the need for perioperative vasoactive drug delivery [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Although adherence to protocol fasting abbreviation was not high, the results showed that, when the shorter fasting was prescribed, length of stay decreased. This association between reduced fasting and accelerated postoperative recovery has been reported by several authors 6,8,10,11 . This change of routine fasting is safe and is recommended by anesthesia societies 12,13 , and revisions made on the subject 14 .…”
Section: Results Results Results Resultsmentioning
confidence: 74%
“…The increased research in the field of cardiac surgery such as the article written by Feguri et al [11], "Results of clinical and metabolic effects of fasting with carbohydrate in coronary artery bypass grafting," and the deepening of the concepts briefly described have great therapeutic potential due to the low cost and easy implementation in daily practice. …”
Section: See Also Original Article On Pages 7-17mentioning
confidence: 99%